2008
DOI: 10.1542/peds.2008-0450
|View full text |Cite
|
Sign up to set email alerts
|

Girls Who Disclose Sexual Abuse: Urogenital Symptoms and Signs After Genital Contact

Abstract: Sexually abused girls who experienced direct genital contact frequently reported symptoms related to the abusive episode. These symptoms were reported most frequently with genital-to-genital contact. This information sheds some light on the mechanism of injury leading to symptom reporting and can be used to further study symptoms/signs reported by sexually abused girls compared with the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 16 publications
1
14
0
4
Order By: Relevance
“…Other less frequent exposures implicated include chlorinated pool water, dysfunctional voiding with maceration, 12,23 masturbation, 10,17 and sexual abuse, specifically inappropriate genital contact, which has been associated with genital soreness, dysuria, and bleeding. 21,24 In this study, the only symptoms associated with genital exposure to soaps, shampoo, bubble baths, and tight-fitting underwear, pants, and bathing suits are dysuria and genital soreness.…”
Section: Discussionmentioning
confidence: 73%
“…Other less frequent exposures implicated include chlorinated pool water, dysfunctional voiding with maceration, 12,23 masturbation, 10,17 and sexual abuse, specifically inappropriate genital contact, which has been associated with genital soreness, dysuria, and bleeding. 21,24 In this study, the only symptoms associated with genital exposure to soaps, shampoo, bubble baths, and tight-fitting underwear, pants, and bathing suits are dysuria and genital soreness.…”
Section: Discussionmentioning
confidence: 73%
“…As much as 21% of the children reported histories of multiple incidence of sexual contact. A delayed disclosure is typical for abuse, and since most injuries that children incur as a result of sexual contact will be superWcial and heal without any lasting residual, most examinations show neither acute nor healed Wndings [34]. It has been conWrmed that a single incomplete hymenal rupture can heal in 9 days and a complete rupture in 24-30 days after the trauma [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Of girls who experienced genital contact, 37% provided history of dysuria that followed the sexual contact [37]. In a recent study, only 2% of 192 girls with a history of vaginal penetration had physical signs (hymenal transection, perforation) [38]. Special attention is required in the cases in which sexual abuse was carried out by a member of the victim's family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a medical history identifying physical M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT symptoms of painful urination may be directly related to a recent episode of sexual abuse and provide additional information of forensic significance. 5 The process of obtaining the history from the child and non-offending caregiver also provides an opportunity to assess fears or concerns related to the abuse 4 and to stress the importance of engaging in evidence-based trauma-focused mental health therapy. A recent study found that trauma symptoms in children were highly associated with the degree of self-blame the child felt about the abuse incident(s), an issue which can be addressed during the medical evaluation.…”
Section: Medical Historymentioning
confidence: 99%